Minimal model for the magnetic phase diagram of CeTi1-xScxGe, GdFe1-xCoxSi, and related materials - Carreras Oropesa, William Gabriel; Encina, Sergio; Pedrazzini, Pablo; Correa, Víctor Félix; Sereni, Julian Gustavo Renzo; Vildosola, Veronica Laura; García García, Jose Daniel; Cornaglia de la Cruz, Pablo Sebastian (Elsevier Science, 2020)
Fil: Carreras Oropesa, William Gabriel. Comisión Nacional de Energía Atómica. Centro Atómico Bariloche; Argentina. Comisión Nacional de Energía Atómica. Gerencia del Área de Energía Nuclear. Instituto Balseiro; Argentina. Universidade de Sao Paulo; Brasil